Exaggerated blood pressure response to fasudil or nifedipine in hypertensive Ren-2 transgenic rats: role of altered baroreflex - Vaněčková, Ivana; Behuliak, Michal; Hojná, Silvie; Kopkan, Libor; Kadlecová, Michaela; Zicha, Josef (Hypertension research, 2019)
Basal calcium sensitization is decreased in spontaneously hypertensive rats, although their blood pressure (BP) response to acute Rho-kinase inhibition is enhanced. Using fasudil (Rho-kinase inhibitor) or nifedipine (L-VDCC blocker), we evaluated the contribution of calcium sensitization and calcium entry to BP maintenance in hypertensive transgenic Ren-2 rats (TGR) focusing on the influence of major vasoactive systems and/or baroreflex efficiency on BP responses to these two drugs. Homozygous TGR and normotensive Hannover Sprague-Dawley (HanSD) control rats aged 5, 11, or 22 weeks were used. The acute BP-lowering effects of fasudil or nifedipine were studied in intact rats, nitric oxide-deficient L-NAME-pretreated rats and rats subjected to combined blockade of the renin-angiotensin system (RAS), sympathetic nervous system (SNS) and nitric oxide synthase (NOS). Fasudil- or nifedipine-induced BP reduction increased during hypertension development in TGR. By contrast, the nifedipine-induced BP response decreased, whereas the fasudil-induced BP response increased with age in HanSD controls. Our data indicated a major contribution of nifedipine-sensitive calcium entry and relative attenuation of calcium sensitization in hypertensive rats compared with normotensive controls. The BP responses to fasudil or nifedipine were enhanced by NOS inhibition and combined blockade in normotensive HanSD rats but not in hypertensive TGR. In conclusion, calcium sensitization is attenuated by endogenous nitric oxide in normotensive HanSD rats but not in hypertensive TGR. Moreover, BP reduction elicited by acute Rho-kinase inhibition is partially compensated by enhanced sympathetic vasoconstriction. The decreased compensation in hypertensive rats with impaired baroreflex efficiency explains their greater BP response to fasudil than in normotensive animals.
Keywords: potkani transgenní; Male; hypertenze; potkani Sprague-Dawley; fasudil; RhoA/Rho kinase pathway; calcium entry; nifedipin; Calcium sensitization; Baroreflex; mužské pohlaví; blokátory kalciových kanálů; nitric oxide; Hypertension; Vasoconstriction; Rats, Transgenic; krysa rodu Rattus; L type voltage-dependent calcium channels; Animals; Calcium Channel Blockers; Nifedipine; krevní tlak; renin-angiotensin systém; zvířata; Renin-Angiotensin System; Rats; Blood Pressure; 1-(5-isochinolinsulfonyl)-2-methylpiperazin; nifedipine; vazokonstrikce; baroreflex; 1-(5-Isoquinolinesulfonyl)-2-Methylpiperazine; Rats, Sprague-Dawley